THU0078 Polymorphisms of the genes encoding CD40 and growth differentiation factor 15 and in the 9P21.3 region in patients with rheumatoid arthritis and cardiovascular disease. (23rd January 2014) - Rantapää Dahlqvist, S.; Ärlestig, L.
Abstract : Background: An increased morbidity and mortality due to cardiovascular disease in patients with rheumatoid arthritis has been identified. Objectives: Genes related to coronary artery disease in the general population, CD40, growth differentiation factor 15 (GDF15) and the 9p21.3 locus were analyzed in patients with rheumatoid arthritis (RA) with respect to atherothrombotic (AT) comorbidity Methods: A cross-sectional study of 681 individuals (498 females; 183 males) with RA (ACR criteria), having a mean age of 60.6±13.2 years and mean disease duration of 15.5±12.6 years, were consecutively recruited and followed up for 6 years. The prevalence of AT manifestations (ATM), [acute myocardial infarction (AMI), angina pectoris with intervention, deep vein thromboses/pulmonary embolism (DVT/PE) and/or stroke/TIA] and hypertension (HT) was registered. Polymorphisms in the gene coding for GDF15, rs1058587 and in CD40 gene, rs1535045 and rs3765459, and the 9p21.3 locus (rs 1333049) were analyzed. Polymorphisms were genotyped using a TaqMan 9700HT and the 5'nuclease allelic discrimination assay. Controls (n=687) were randomly selected and matched for age and gender from the Medical Biobank of Northern Sweden. Results: The distribution of the genotype of GDF15 differed significantly between patients with RA and controls (p=0.034, odds ratio (X2=6.40, 2df, p<0.05). During the follow up were 149 new AT events were registered. Overall ATM was predicted by carriage of the GG genotype of GDF15 and also by the rare genotype of 9p21.3, Odds ratio (OR)=2.21 (95%CI 1.17-4.18, adjusted) and 1.92 (95%CI 1.15-3.19, adjusted), respectively. 9p21.3 genotype predicted also a new AT event during the follow up (OR=2.46, 95%CI 1.29-4.7). The minor allele and genotype GG of GDF15 were related to stroke/TIA in female patients (OR=3.75, 95%CI 1.06-13.33, adjusted). Male patients homozygous for major allele of CD40, CC in rs1535045 (OR=6.48, 95%CI 1.31-32.00, adjusted) and GG in rs3765459 (OR=3.45 95%CI 1.21-9.85, unadjusted, OR=2.78, 95%CI 0.78- 9.91, adjusted) were more often affected by stroke. The adjustments were HLA-shared epitope, disease activity, anti-citrullinated antibodies/rheumatoid factor, HT, diabetes and treatments, smoking and age. Conclusions: The gene polymorphisms analysed were associated with different manifestations of AT events in RA. The GDF15 gene polymorphism was also associated with RA per se suggesting a common aetiology for RA and ATM. Disclosure of Interest: None Declared